1989
DOI: 10.1172/jci114246
|View full text |Cite
|
Sign up to set email alerts
|

A physiologic role for somatostatin 28 as a regulator of insulin secretion.

Abstract: Somatostatin 28 (S-28) is a peptide produced in the intestinal tract which rises in the circulation during nutrient absorption. We tested the hypothesis that S-28 regulates B-cell function by (a) studying the effects on insulin secretion of "physiologic" infusions of S-28 and (b) measuring insulin responses during elevated nutrient-stimulated endogenous S-28 levels. (a) Synthetic S-28 was infused on separate days into six healthy men at rates of 25 and 50 ng/kg per h which mimicked postprandial levels. Subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 33 publications
1
21
0
Order By: Relevance
“…Thus, neither S-14 nor its conversion product S-13 is likely to serve as a hormone outside the splanchnic bed. However, based on inhibition of insulin release by S-28 infused to achieve postprandial levels in humans (18,19), coupled with the present findings, a creditable case can be made for S-28 as a humoral signal to islet B cells. S-28 is a potent inhibitor of insulin release, both in vivo and in vitro (38)(39)(40)(41), with a high binding affinity for B cells (42,43).…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Thus, neither S-14 nor its conversion product S-13 is likely to serve as a hormone outside the splanchnic bed. However, based on inhibition of insulin release by S-28 infused to achieve postprandial levels in humans (18,19), coupled with the present findings, a creditable case can be made for S-28 as a humoral signal to islet B cells. S-28 is a potent inhibitor of insulin release, both in vivo and in vitro (38)(39)(40)(41), with a high binding affinity for B cells (42,43).…”
Section: Discussionmentioning
confidence: 63%
“…Thus, we hypothesized that S-28 is a regulator of glucose metabolism during the postprandial state. In earlier studies, we showed that infusion of S-28 in humans inhibited both the secretion of insulin from pancreatic B cells and the products of pancreatic acinar cells (18,19). Although these results support a physiologic role for S-28, a more compelling approach is to prevent the peptide from accessing its receptors and, thereafter, evaluate any changes in the release of products from the putative target cell (20)(21)(22).…”
Section: Somatostatin-14 (S-14)mentioning
confidence: 97%
“…Somatostatin-28 (SST-28) is a peptide derivative of the pro-somatostatin gene that is expressed widely, including in gastrointestinal cells and pancreatic islet cells. Islet somatostatin signaling is thought to be principally paracrine, rather than endocrine, and serum SST-28 concentrations increase post-prandially (D’Alessio et al, 1989; Strowski and Blake, 2008). Galanin is an orexigenic neuropeptide produced throughout the CNS and in peripheral neurons, and has been reported to inhibit insulin secretion (Fehmann et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…It has been postulated that the postabsorptive increase of SST secretion may provide a mechanism to prevent excessive glucagon secretion (D'Alessio et al, 1989;Klaff and Taborsky, Jr. 1987). However, the role of pancreatic SST in inhibiting glucagon secretion may be more relevant in the basal state, because anti-SST enhanced glucagon output from the perfused human pancreas only at low glucose concentrations (Brunicardi et al, 2001;Kleinman et al, 1994).…”
Section: Page 5 Of 29mentioning
confidence: 99%